2021
DOI: 10.3390/ma14020311
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Mechanical Properties, and Corrosion Behavior of Ultra-Low Carbon Bainite Steel with Different Niobium Content

Abstract: Four types of ultra-low carbon bainite (ULCB) steels were obtained using unified production methods to investigate solely the effect of niobium content on the performance of ULCB steels. Tensile testing, low-temperature impact toughness testing, corrosion weight-loss method, polarization curves, electrochemical impedance spectroscopy (EIS), and the corresponding organizational observations were realized. The results indicate that the microstructure of the four steels comprise granular bainite and quite a few m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…in the steel having a better corrosion resistance [12][13][14]. It can be seen from Table 2 that the 1# specimen with a Cu-Sb composite added to it had the lowest capacitance value and the highest Rf value, thus indicating that its resistance to electrochemical corrosion increased after low alloying [15].…”
Section: Eis Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…in the steel having a better corrosion resistance [12][13][14]. It can be seen from Table 2 that the 1# specimen with a Cu-Sb composite added to it had the lowest capacitance value and the highest Rf value, thus indicating that its resistance to electrochemical corrosion increased after low alloying [15].…”
Section: Eis Resultsmentioning
confidence: 99%
“…This indicates that the selected equivalent circuit was effective in fitting the elements. The size of the impedance arc represents the ease of the charge transfer, with a larger diameter indicating a higher R f value (suggesting that the corrosion reaction is less likely to occur), which thus results in the steel having a better corrosion resistance [12][13][14]. It can be seen from Table 2 that the 1# specimen with a Cu-Sb composite added to it had the lowest capacitance value and the highest R f value, thus indicating that its resistance to electrochemical corrosion increased after low alloying [15].…”
Section: Potentiodynamic Polarization Resultsmentioning
confidence: 99%
“…The corrosion behavior of the ferrite–bainite dual‐phase steel is associated with the volume fraction of each phase. Zong et al [ 18 ] reported that Nb microalloying affects the bainite morphologies and the corrosion behavior. It is well known that martensite, bainite, and ferrite have the similar crystal structure (i.e., body‐centered cubic structure), but have different dislocation density, carbon content, and morphology.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of those alloying elements can facilitate the formation of a dense and strongly adherent rust layer during wet/dry cycles. Compared to plain carbon steels (CS), the corrosion resistance of WS is enhanced due to the protective rust layer [ 1 , 2 , 3 , 4 ]. This contributes to the application for WS in bridge structures (e.g., orthotropic steel decks) ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%